2018
DOI: 10.1111/cas.13800
|View full text |Cite
|
Sign up to set email alerts
|

Association of antithyroglobulin antibodies with the development of thyroid dysfunction induced by nivolumab

Abstract: Thyroid dysfunction (TD) induced by immune checkpoint inhibitors is not sufficiently understood. The purpose of this retrospective observational study was to identify risk factors and the clinical course of TD induced by nivolumab. Patients with advanced solid tumors who were treated with nivolumab from March 2009 through to March 2016 at the National Cancer Center Hospital (Tokyo, Japan) were included. Thyroid function and antithyroid Abs from serum samples among all patients were evaluated at baseline and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 35 publications
6
84
3
2
Order By: Relevance
“…The frequency of irAEs has previously been shown to increase in patients with a history of autoimmune disease who were administered with an immune checkpoint inhibitor. Furthermore, the frequency of anti‐PD‐1 antibody‐induced thyroid dysfunction appears to increase in the presence of baseline thyroid‐related autoantibody positivity . A relationship between antinuclear antibodies and immune checkpoint inhibitors with respect to safety has not been reported to date, and the present data indicate that these factors are not correlated.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The frequency of irAEs has previously been shown to increase in patients with a history of autoimmune disease who were administered with an immune checkpoint inhibitor. Furthermore, the frequency of anti‐PD‐1 antibody‐induced thyroid dysfunction appears to increase in the presence of baseline thyroid‐related autoantibody positivity . A relationship between antinuclear antibodies and immune checkpoint inhibitors with respect to safety has not been reported to date, and the present data indicate that these factors are not correlated.…”
Section: Discussioncontrasting
confidence: 44%
“…Furthermore, the frequency of anti-PD-1 antibody-induced thyroid dysfunction appears to increase in the presence of baseline thyroid-related autoantibody positivity. 20,21 A relationship between antinuclear antibodies and immune checkpoint inhibitors with respect to safety has not been reported to date, and the present data indicate that these factors are not correlated. A substantial proportion of patients were found to express PD-L1 in the present study, and previous data have suggested that these patients might be at increased risk of a poorer prognosis.…”
Section: Horinouchi Et Alcontrasting
confidence: 48%
“…It is possible that activation of pre-existing autoimmunity against thyroid glands is involved in the pathogenesis of thyroid dysfunction induced by ICIs. For example, the incidence of thyroid dysfunction is reportedly higher in patients who have anti-thyroglobulin antibodies (TgAb) and/or anti-thyroid peroxidase antibodies (TPOAb) prior to the initiation of the treatment with nivolumab than in patients without these antibodies [22,23]. In most cases of thyroid dysfunction induced by ICIs, thyroid ultrasonography shows diffuse enlargement of the thyroid gland accompanied by decreased internal blood flow and low internal echogenicity, while thyroid scintigraphy shows decreased uptake of isotope, suggestive of destructive thyroiditis.…”
Section: Overviewmentioning
confidence: 99%
“…In clinical practice, it would be beneficial to identify, in advance, which patients are at greatest risk of developing an endocrine irAEs induced by an ICI. It has been reported that the presence of TgAb and/or TPOAb in serum may be potential biomarkers of thyroid dysfunction induced by the anti-PD-1 antibody [22,23]. On the other hand, there are no reports to date that have shown predictive biomarkers for endocrine irAEs other than thyroid dysfunction.…”
Section: Commentsmentioning
confidence: 99%
“…ICI‐related TAEs have been variously described as hyperthyroidism and/or hypothyroidism (both overt and subclinical) and/or as a destructive thyroiditis with an initial phase of thyrotoxicosis, which may evolve to transient or permanent hypothyroidism . According to previous studies, 12% of patients had the typical course of destructive thyroiditis. Lee et al describe the evolution of thyroiditis in 20% of patients treated with anti‐PD‐1 monotherapy.…”
Section: Discussionmentioning
confidence: 99%